Exploring Latino Parent and School Staff Perspectives on Latino Parent Involvement in Public Schools - Daughtridge, Sarah E (East Carolina University, 2019)
The purpose of this qualitative study was to explore experiences and culturally appropriate practices of Latino parents' participation in the public school system. The study also explored school staff perceptions and actions toward Latino parents' school involvement. The study's exploration rests on Epstein (2001) theoretical framework of parent-school involvement. Focus group data were collected in Spanish from 37 Latino parents of students enrolled in six K-12 public schools with at least 11% Latino student's enrollment in eastern North Carolina. Individual interviews were conducted with 11 school officials from three different public schools. Data were transcribed, analyzed (Creswell & Creswell, 2018) and entered into NVIVO version 12 for formal coding. Three major themes emerged from parent data: inadequate communication, low Latino representation, and need for cultural competency. Also, three themes emerged from school staff data: inadequate communication, engagement of county school system, and parental involvement. Suggested strategies to improve the parent/teacher relationship and promote parental involvement in the public school were more trained interpreters, translated materials in Spanish, Latino parent committee, and welcoming environment. Both school staff and parents expressed the need for Latino cultural awareness. School staff expressed the need for Latino parents' active engagement in school events, parent teacher conference, and reaching out to teachers to discuss children school needs. These results have implications toward bridging the gap between Latino parents and public schools.
Keywords: Public Schools; Education--Parent participation; Hispanic Americans--Education; Academic achievement